An investigation into the optimal device design for selenium solar cells - L. Thomas; C.H. Don; J.D. Major (Energy Reports, 2022)
Despite a resurgence in recent years, the optimal device design for selenium solar cells is still not known with individual studies using significantly different window layers, hole transport layers and selenium absorber thicknesses. In this work we present results comparing the effect of each of these on device performance and propose that the ideal absorber thickness is influenced by the specific device structure being utilized. A TiO2 window layer and P3HT hole transport layer with a 200 nm Se absorber layer was found to produce the best performance of 2.1% from materials investigated in this study, however performance remains limited due to the presence of an interfacial charge extraction barrier apparent from current–voltage analysis.